2021
DOI: 10.1186/s13054-021-03501-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-intensive care syndrome among Japanese intensive care unit patients: a prospective, multicenter, observational J-PICS study

Abstract: Background Many studies have compared quality of life of post-intensive care syndrome (PICS) patients with age-matched population-based controls. Many studies on PICS used the 36-item Short Form (SF-36) health survey questionnaire version 2, but lack the data for SF-36 values before and after intensive care unit (ICU) admission. Thus, clinically important changes in the parameters of SF-36 are unknown. Therefore, we determined the frequency of co-occurrence of PICS impairments at 6 months after… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 63 publications
4
115
1
3
Order By: Relevance
“…They examined 3,151 patients who stayed in the ICU for more than 24 hours and revealed an 18% PTSD prevalence, which was significantly higher than our rate. However, their median APACHE score was 15 (11)(12)(13)(14)(15)(16)(17)(18)(19), which was comparable to that in our study population. A recent systematic review also suggested that illness severity was not associated with the development of PTSD [19]; thus, it is unlikely that mental illness severity at admission contributed to the difference in the prevalence of PTSD between our study and previous studies.…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…They examined 3,151 patients who stayed in the ICU for more than 24 hours and revealed an 18% PTSD prevalence, which was significantly higher than our rate. However, their median APACHE score was 15 (11)(12)(13)(14)(15)(16)(17)(18)(19), which was comparable to that in our study population. A recent systematic review also suggested that illness severity was not associated with the development of PTSD [19]; thus, it is unlikely that mental illness severity at admission contributed to the difference in the prevalence of PTSD between our study and previous studies.…”
Section: Plos Onesupporting
confidence: 82%
“…Although this prevalence was consistent with that reported in a previous systematic review [ 7 ], the population did not reflect the general ICU population in Japan. Kawakami and colleagues [ 11 ] reported the effects on physical and mental QOL, as measured by the Short Form 36, and cognitive impairment after 6 months among 96 patients who required mechanical ventilation (MV) for more than 48 hours in 16 ICUs in Japan. However, they did not clarify the prevalence of PTSD, anxiety, or depression.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged physical impairments occur in approximately 30% of ICU survivors 3-6 months after critical illness [5,6]. The 6-min walk test outcomes deteriorate below the normal level at the mean distances of 361 m at 3 months and at 411 m at 60 months after discharge [9].…”
Section: Physical Impairmentsmentioning
confidence: 99%
“…PICS is the collective manifestation of a prolonged physical impairment, cognitive impairment, and mental health problems that occur during or after intensive care unit (ICU) stay and affects not only the long-term outcomes of ICU patients but also the mental health of the patients' families [4]. Individual PICS symptoms have been reported to develop in 50-70% of critically ill patients, and their co-occurrence has been approximately evidenced in 20% of patients [5,6]. It is known that the QOL of patients decreases with the onset of PICS, and approximately two-thirds, two-fifths, and one-third of previously employed ICU survivors are jobless up to 3, 12, and 60 months following hospital discharge [3].…”
Section: Introductionmentioning
confidence: 99%
“…A case series analysis in COVID-19 patients [9] reported a higher rate (75%) of delirium but a lower incidence of cognitive impairment and a higher 6 min walk distance at the 6 week follow-up than in non-COVID ARDS patients, quite similar to our findings. Previously, it was reported that the prevalence of PICS among ICU patients in Japan was 63.5%, and 32%, 15%, and 38% had physical, mental, and cognitive impairment, respectively, [10] indicating that the prevalence of psychological disorders was higher in that study. Dinglas and colleagues reported that 38% of patients with non-COVID-19 ARDS had significant muscle weakness at hospital discharge, sustained muscle weakness was found in 50%, and muscle weakness had an impact on the 5-year survival rate.…”
Section: Discussionmentioning
confidence: 56%